Mathematics Learning Practice Training with the "MiKIR" Approach to Improve Analysis and Algebra Reasoning Abilities in Mathematics MGMP SMP Sragen - Pramudya, Ikrar; Mardiyana, Mardiyana; Sutrima, Sutrima; Sujatmiko, Ponco; Aryuna, Dyah Ratri (Journal of Mathematics and Mathematics Education, 2020)
The curriculum currently applied at the junior high school level is Curriculum 2013. This curriculum focuses on student learning activities. In a sense, knowledge must be actively built by students themselves. This paradigm has been known for a long time. At least since the introduction of the concept of active student learning in 1984 by Professor Dr. Conny R. Semiawan. However, in reality the teaching and learning process that occurs is that the teacher remains the center of attention when the teaching and learning process takes place in the classroom. In other words, those who are active in learning are still teachers and students sitting quietly listening to the teacher's explanation. The challenge is whether mathematics teachers are willing and brave to change the mindset from "teacher as a learning center" to "students as a learning center". To create a teaching and learning process with "students as the learning center", of course, it must be started from the making of the learning design to the practice of its application in the learning process in the classroom. In line with these wishes and intentions, this service activity answered by providing "Training and Assistance in Mathematics Learning Practices with the" MiKIR "Approach to Improve Analytical and Algebraic Reasoning Ability for mathematics teachers who are members of the Mathematics MGMP SMP Sragen Regency. In this case, the "MiKIR" approach is interpreted as a learning approach which, when applied in a teaching and learning process, occurs in students’ situations and conditions: experiencing, interaction, communication, and reflection both between students and students and students and teachers and that means "Students as a learning center".